2018
DOI: 10.1007/s00264-018-4097-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bearing surfaces on periprosthetic hip infections: analysis of thirty nine thousand, two hundred and six  cementless total hip arthroplasties

Abstract: Bearing surfaces influenced the rate of PHI; in particular, stemmed MOM implants were at higher risk, probably due to metal debris consequent to taperosis. Despite the preliminary results, stemmed MOM THAs should be used with care, and diabetic patients should be warned about increased septic risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Metal-on-metal interfaces are more prone to infections, probably due to necrosis and immunomodulation induced by metal particle release (Bordini et al. 2019). Mixing metals may even worsen the local situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal-on-metal interfaces are more prone to infections, probably due to necrosis and immunomodulation induced by metal particle release (Bordini et al. 2019). Mixing metals may even worsen the local situation.…”
Section: Discussionmentioning
confidence: 99%
“…The Register of Prosthetic Orthopedic Implants (RIPO) is a regional database (surveillance over 4,500,000 inhabitants) recording clinical conditions of patients, surgical procedures, implant characteristics, i.e., fixation, head size and material, and type of acetabular cup and stem (RIPO 2018, Bordini et al. 2019). Primary and revision hip and knee replacement surgeries are included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For what concerns primary total hip arthroplasty (THAs), it has been reported that the number of interventions of this kind performed in the United States continues to increase each year, as does the incidence of infectious complications. The changing profile of antibiotic resistant bacteria has made preventing and treating primary THA infections increasingly complex [18].…”
Section: Discussionmentioning
confidence: 99%
“…Also, periprosthetic hip infections are correlated with metal-on-metal (MoM) coupling, particularly in stemmed implants and with higher risks, probably due to metal debris consequent to taperosis. Despite the preliminary results, stemmed MoM THAs should be used with care and diabetic patients should be warned about increased septic risks [13].…”
Section: Hipmentioning
confidence: 97%